2020
DOI: 10.1177/1553350620953023
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Using Staplers and Vessel Sealing Devices for Laparoscopic Splenectomy: A Randomized Controlled Trial

Abstract: Background. Laparoscopic splenectomy (LS) is considered the operation of choice on elective basis for managing patients with certain hematological disorders. Hemostatic control of the splenic pedicle is one of the crucial steps in LS. This study compares the safety and efficacy of using endoscopic staplers and vessel sealing devices to control the splenic pedicle in patients with nonsevere splenomegaly. Methods. Fifty-one consecutive patients with different blood disorders including idiopathic thrombocytopenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
(29 reference statements)
0
12
0
Order By: Relevance
“… 13 , 14 Newer surgical energy devices, including the Valley Lab LigaSure vessel‐sealing system and Ethicon Harmonic Scalpel, reduce blood loss and operative time. 15 , 16 Three investigators have reported a reduced number of bleeding complications when preoperative splenic artery embolization was performed. 17 , 18 , 19 Elective splenectomy allows vaccination to be completed at least 2 weeks preoperatively; if vaccination has not been performed preoperatively, an 8‐week interval is recommended prior to postoperative vaccination of the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 14 Newer surgical energy devices, including the Valley Lab LigaSure vessel‐sealing system and Ethicon Harmonic Scalpel, reduce blood loss and operative time. 15 , 16 Three investigators have reported a reduced number of bleeding complications when preoperative splenic artery embolization was performed. 17 , 18 , 19 Elective splenectomy allows vaccination to be completed at least 2 weeks preoperatively; if vaccination has not been performed preoperatively, an 8‐week interval is recommended prior to postoperative vaccination of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons advocate for single‐port laparoscopy as it provides a larger incision for spleen extraction 13,14 . Newer surgical energy devices, including the Valley Lab LigaSure vessel‐sealing system and Ethicon Harmonic Scalpel, reduce blood loss and operative time 15,16 . Three investigators have reported a reduced number of bleeding complications when preoperative splenic artery embolization was performed 17–19 .…”
Section: Discussionmentioning
confidence: 99%
“…All eligible studies were screened for their methods, characteristics, and risk of bias strictly. [15–20]…”
Section: Methodsmentioning
confidence: 99%
“…All eligible studies were screened for their methods, characteristics, and risk of bias strictly. [15][16][17][18][19][20] In this meta-analysis, 2 different kinds of groups were generated from the included papers that met the criteria of the LigaSure group and the convention group. The convention method referred to traditional methods of excision and hemostasis, including ultrasonic coagulation + EndoGIA, clip, and silk suture ligation.…”
Section: Search Strategy and Selection Of Papersmentioning
confidence: 99%
See 1 more Smart Citation